Anti-CCP antibodies are associated with early age at onset in patients with rheumatoid arthritis (2011)
Objectives: To determine factors influencing the age at onset of rheumatoid arthritis (RA). Methods: A sample of 152 Colombian patients was investigated. Hazard ratios (HRs) that measured the effect size of risk factors on the age at RA onset were computed by using Cox regression models. Results: Positive anti-CCP antibodies were associated with an increased risk of early RA onset (HR=1.60; 95% confidence interval, [1.06, 2.4]), whereas the presence of the protective 70DERAA74 sequence was associated with a delayed onset (HR=0.55; [0.33, 0.92]). After controlling for both anti-CCP antibodies and the 70DERAA74 sequence, the following variables did not influence significantly the age at RA onset: gender, ever cigarette smoking, family RA history, the TNF-308 A polymorphism, HLA shared epitope, and the presence of rheumatoid factor. Conclusion: Anti-CCP antibodies and the HLA-DRB1 70DERAA74 sequence influence the age at onset of RA. © 2010 Société française de rhumatologie.